Avoidance behaviour of Enchytraeus albidus: effects of Benomyl, Carbendazim, phenmedipham and different soil types - Amorim, Mónica J. B.
Enchytraeids are typical inhabitants of many soils, contributing to vital processes of this environmental compartment. Indirectly they are involved in regulating the degradation of organic matter, as well as improving the pore structure of the soil. Due to their behaviour, they are able to avoid unfavourable environmental conditions. Avoidance tests with enchytraeids, initially developed with earthworms by several authors, are quick and easy to perform. With these tests a first assessment of the toxicity of a (contaminated or spiked) soil is possible in just 4 8 h by using the reaction of the enchytraeids as measurement endpoint. In this period of time the organisms can choose between the control soil and the other soil (a contaminated or spiked or another soil with different physico-chemical properties). In the tests reported h ere, the enchytraeids were exposed to control soils spiked with the fungicides Benomyl and Carbendazim and the herbicide Phenmedipham. Several chemical. concentrations were tested in order to evaluate the avoidance behaviour to toxic substances. In fact, often these short-term screening tests gave results showing avoidance at concentrations in a range similar to the acute test results but, higher than in chronic tests. Further tests are needed to decide whether the results gained in this study can be extrapolated to other chemicals. It is proposed to standardize the Enchytraeid Avoidance Test as it is currently done for the Earthworm Avoidance Test by the International Standard Organization (ISO). (c) 2005 Elsevier Ltd. All rights reserved.